GÊNERO, TRÁFICO SEXUAL DE MULHERES E POLÍTICAS PÚBLICAS: uma análise da experiência da Secretaria de Políticas para as Mulheres da Presidência da República (SPM/PR) - LIMA, Thiago Pereira (2017)
The women‘s sexual traffic presents as one practice that occurs in several countries, in different scales and dynamics. The debate about public policies of traffic‘s fighting emerge in the end of 20‘s century, with the Additional Protocol to the United Nations Convention against Transnational Organized Crime related to the prevention, repression and punishment of Trafficking Persons, in special Women and Children - the Palermo Protocol (2000). Brazil has been influenced by the Palermo Protocol and builds the National Policy in Fighting the Traffic of People (2006), the 1st National Plan in Fighting the Traffic of People (2008) and the 2nd National Plan in Fighting the Traffic of People (2013). The thesis argues the assumptions that demonstrates the national and supranational legal devices, as well as the Brazilian public policies in fighting the women‘s sexual traffic, taking into account as the perspective of gender that has been built on debate. Therefore, taking as reference, the international documents that Brazil was signatory over 20‘s century, the Palermo Protocol (2000), the Brazilian policies developed in the first decade of 21‘s century, from the National Policy in Fighting the Traffic of People, the 1st National Plan in Fighting the Traffic of People and the 2nd National Plan in Fighting the Traffic of People, as well as interviews with official policies as the Women‘s Secretariat of Policies (SPM/PR) and Ministry of Justice (MJ) and the Human Rights Secretariat (SEDH). I analyze the speech and actions developed by the Women‘s Secretariat of Policies of the Presidency of the Republic (SPM/PR), created in 2003, on the scope of Federal Government to develop state‘s policies to reach the fightning related to the violence against women. According with the empirical datas and in a theoretical perspective in gender studies, I argue that public policies presents a gender perspective, limited to women and not in a relational perspective; there is a speech and generalized actions that don‘t meet the complex field of gender, according it shows the official reports and the interviews made with the competent bodies. The speech and the actions in fighting the women‘s sexual traffic reproduces the international line and considering the traffic inside the actions in fighting the violence against women. The public policy creates movements of essentials, producing ambiguous effects, due to the same time, it meets the needs of vulnerable segments, as women, and in the other side, it doesn‘t meets the plurality.